PENGARUH KURS RUPIAH, TINGKAT SUKU BUNGA, DAN TINGKAT PENGANGGURAN TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR PERTAMBANGAN MINYAK DAN GAS BUMI YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE 2012-2017 - Dewi, Atika Puspita; Asakdiyah, Salamatun (Universitas Ahmad Dahlan, 2018)
The monetary situation and the movement of macroeconomic variables are things that must be considered an investor in the stock trading activity in a country. The economic situation and fluctuations in macro variables in one country can affect the stock price, including the oil and gas mining sub-sector. This study aimed to examine the effect of macroeconomic variables, namely exchange rate, interest rate, and unemployment rate to stock prices. This study uses quantitative methods. The population in this study are all oil and gas mining sub-sector companies listed in Indonesia Stock Exchange in the period 2012-2017. Sample selection technique is by using purposive sampling method. Based on predetermined criteria, acquired 7 oil and gas mining sub-sector companies sampled in this study. Data analysis techniques in this study using multiple linear regression analysis. The results showed that the variables simultaneously exchange rate, interest rate, and unemployment rate significant effect on stock price of oil and gas mining sub-sector companies. Partially, variable Exchange Rate and Interest Rate was a significant influence on stock price, while the variable Unemployment Rates no significant influence on stock price.